Implementation of the Chemo-Entrepreneurship Approach in Chemistry Learning: Systematic Review 2016–2023 - Aqilatun Ni'mah; Suwardi Suwardi (Postgraduate, University of Mataram, 2023)
Chemistry focuses on students understanding the principles, theories, concepts, and laws of chemistry and their application in real life, one of which is through the Chemo-Entrepreneurship (CEP) approach. This research aims to synthesize research related to CEP which focuses on research in chemistry learning. The research method used is Systematic Review (SR) by searching the Google Scholar and IOPscience databases from various journals and proceedings of national and international repute over the last eight years (2016-2023). Based on the search results, 46 relevant articles were obtained to be studied systematically. The research results show that 21.73% of the chemical topics that are widely applied in the CEP approach are colloidal systems. The concept of the CEP approach is contextual, which is linked to real objects, where students can learn the process of processing a material, packaging, and marketing products related to the material being taught. Effective implementation of the CEP approach through integrating learning media with various learning models. Thus, it is hoped that conducting this research will provide knowledge to teachers regarding the application of the chemo-entrepreneurship approach in chemistry learning